2012
DOI: 10.2183/pjab.88.266
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal dysfunction with aging and its amelioration

Abstract: The author focused on the functional decline of synapses in the brain with aging to understand the underlying mechanisms and to ameliorate the deficits. The first attempt was to unravel the neuronal functions of gangliosides so that gangliosides could be used for enhancing synaptic activity. The second attempt was to elicit the neuronal plasticity in aged animals through enriched environmental stimulation and nutritional intervention. Environmental stimuli were revealed neurochemically and morphologically to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Changes in ganglioside composition with age also occur in liver [ 68 ]. There are only indications on the functional consequences of such changes [ 23 ].…”
Section: Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in ganglioside composition with age also occur in liver [ 68 ]. There are only indications on the functional consequences of such changes [ 23 ].…”
Section: Occurrencementioning
confidence: 99%
“… Structure of GQ1b, one of the most abundant gangliosides in adult human brain, which is involved in long term potentiation, synaptic plasticity, and improvement of cognitive function [ 23 ]. …”
Section: Figurementioning
confidence: 99%
“…The present synaptophysin accumulations might also be linked to an increased synapse formation, which could be further enhanced by the increased number of neuronal processes resulting in an enlarged contact area of the DRG neurons. Similarly, previous studies demonstrated that gangliosides have an impact on the synaptic plasticity and function of rat hippocampal neurons and thereby influence long term potentiation and learning ability 107 . Formation and maintenance of synapses are dependent on various retrograde messengers including neurotrophins 108 .…”
mentioning
confidence: 60%
“…1,2 In aged conditions, many physical, biological, chemical, neurophysiological and neuropathological changes occur due to loss in synaptic plasticity, synaptic dysfunction, which further leads to subsequent triggering of neurodegenerative processes. 3 The growing need for the treatment of cognitive impairment due to aging or dementia has led to the search for potential cognition enhancing drugs. The various compounds presently under development represent an alternative to cholino-mimetic therapy and include new chemical entities as well as piracetam and its newer analogs.…”
Section: Introductionmentioning
confidence: 99%